2020
DOI: 10.1136/bmjgh-2020-003564
|View full text |Cite
|
Sign up to set email alerts
|

Labour companionship and women’s experiences of mistreatment during childbirth: results from a multi-country community-based survey

Abstract: BackgroundEvidence has shown the benefits of labour companions during childbirth. Few studies have documented the relationship between the absence of labour companions and mistreatment of women during childbirth in low-income and middle-income countries using a standardised tool.MethodsWe conducted a secondary analysis of the WHO multi-country study on how women are treated during childbirth, where a cross-sectional community survey was conducted with women up to 8 weeks after childbirth in Ghana, Guinea, Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 33 publications
(89 reference statements)
0
37
1
Order By: Relevance
“…Our findings from the labour observations are consistent with the community survey data within the same WHO multicountry study, which showed that the association between some types of mistreatment (ie, physical abuse, verbal abuse, poor communication and the absence of a labour companion) also varied by country. 29 Absence of a labour companion was associated with non-consented vaginal examination in Ghana and Guinea but not Nigeria, which only showed a significant association with decreased waiting time. 29 In this study, non-consented vaginal examination was generally high across all the three countries, ranging from approximately 50% in Guinea to nearly 70% in Nigeria.…”
Section: Discussionmentioning
confidence: 90%
“…Our findings from the labour observations are consistent with the community survey data within the same WHO multicountry study, which showed that the association between some types of mistreatment (ie, physical abuse, verbal abuse, poor communication and the absence of a labour companion) also varied by country. 29 Absence of a labour companion was associated with non-consented vaginal examination in Ghana and Guinea but not Nigeria, which only showed a significant association with decreased waiting time. 29 In this study, non-consented vaginal examination was generally high across all the three countries, ranging from approximately 50% in Guinea to nearly 70% in Nigeria.…”
Section: Discussionmentioning
confidence: 90%
“…This analysis as well as other in depth analyses of the study findings have identified substantial differences in how mistreatment is experienced in distinct healthcare settings and how forms of mistreatment may be linked. 54 As a whole, this body of work confirms that mistreatment is complex and cannot be measured by only one or two items standardised across populations and health system settings. Interventions to reduce mistreatment will require context-specific understanding of mechanisms and drivers within the health system.…”
Section: Discussionmentioning
confidence: 68%
“…Another attitude identified by the participants in this study was that a relative should accompany the woman in case of complications during pregnancy or childbirth. It represents a major psychological support for the woman in labor [22]. According to Peprah et al [21], acceptance of support is easier when the delivery is carried out by a traditional birth attendant.…”
Section: ) Knowledgementioning
confidence: 99%